Action of a cationic surfactant on the activity and removal of bacterial biofilms formed under different flow regimes - Simões, M. (2005)
The action of the cationic surfactant cetyltrimethylammonium bromide (CTAB) was investigated to control biofilms (aged 7 d) formed by Pseudomonas fluorescens on stainless-steel slides, using flow cells reactors, under turbulent and laminar flow. The effect of CTAB was also investigated using planktonic cells in the presence and absence of BSA, by measuring the cellular respiratory activity and the ATP released. The action of CTAB on biofilms was assessed by means of cellular respiratory activity and variation of biofilm mass, immediately and 3, 7 and 12 h after the application of CTAB. The physical stability of the biofilm was also assessed using a rotating device, where the effect of the surfactant on the biofilm stability was evaluated through the variation of the mass remaining on the surface. CTAB significantly reduced the activity of the planktonic cells probably due to the rupture of the cells. This effect was significantly reduced in the presence of BSA. Planktonic cells were more easily inactivated than bacteria in biofilms. Biofilms formed under laminar flow were more susceptible than those formed under turbulent flow, but in both cases total inactivation was not achieved. Biofilm recovery was observed, in terms of respiratory activity, in almost all the cases studied. CTAB application by itself did not promote the detachment of biofilms. The physical stability tests showed that the synergistic action of the surfactant and the application of high shear stress to the biofilm increase its detachment.